Revitalization the Internal Quality Assurance Through Leadership, Commitment, and Organization Culture - Amtu, Onisimus; Fakhruddin, Fakhruddin; Haryono, Haryono; Muhsin, Muhsin (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This research aims to determine whether there is a direct and indirect influence on exogenous variables, namely leadership and organizational commitment to endogenous variables, namely the application of internal quality assurance systems in state universities with organizational culture as an intervening variable. This research used quantitative approach and the analysis tools is path analysis. Population of this study included 340 lecturers at three state universities in Ambon and the sample size was 221 respondents.Â The results of the study prove that organizational culture plays an important role in mediating and contributing to leadership and organizational commitment to the implementation of the internal quality assurance system in higher education. Leadership and organizational commitment require an organizational culture to build communication and motivation through expectations and academic values that develop in a healthy, creative, innovative and dynamic manner because it can encourage collaboration and synergy of all elements of higher education to achieve the set quality standards.